Pengenalan Dan Pencegahan Pre Menstrual Syndrome Pada Remaja Putri Di Man Malakaji Kabupaten Gowa - Pratiwi Bayuningrum; Safira Welay; Syahruni Syahruni; Nirwana Nirwana (Pusat Riset dan Inovasi Nasional, 2023)
Young women are said to have entered the puberty phase, one of which is marked by menstruation. Menstruation is actually a natural, progressive and positive biological symptom as a biological sign of sexual maturity. So this incident should be accepted with a reasonable attitude. However, menstruation usually has disorders, one of which is premenstrual disorder which is usually called Premenstrual Syndrome. The impact that arises due to PMS symptoms is that female students lose interest in doing activities and sleep more during class. The female student explained that the stress she experienced was usually due to a large load of lessons and school assignments, interactions with peers, and personal problems. Providing good knowledge to support their readiness in dealing with PMS to increase the knowledge of young women. The results of the t-test carried out showed that the value increased after the introduction and prevention of pre-menstrual syndrome. From these results it can be proven that counseling or providing education has a positive impact, namely increasing the average knowledge of teenagers about Premestrual Syndrome